Pengaruh Harga, Desain, Kualitas Produk terhadap Kepuasan Konsumen (Studi Kasus pada Toko Oleh-Oleh Souvenir Mutmainnah) - Putri Patrianim; Muhajirin Muhajirin (Universitas Serambi Mekkah, 2023)
To be able to win the competition, companies must provide satisfaction to their customers by providing cheaper prices, attractive designs and good quality. This research was taken with the aim of finding out the influence of price, design and product quality on consumer satisfaction with Mutmainnah souvenir figures. This research has quantitative data with the type of research chosen being associative, then the primary data source is obtained from a Likert scale questionnaire as the research instrument. The research population is all consumers of the Mutmainnah souvenir shop in Bima City whose exact number is unknown (Unknown Population) with a sample of 50 people and using a purposive sampling technique. Data was collected through observation, questionnaires and literature study. Then the data was analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficients, determination tests, t tests and f tests. Hypothesis test results show that price, design and product quality influence consumer satisfaction at the Mutmainnah souvenir shop.